A Comprehensive Study on Environmental Issues on the Nature and Human Beings (International Journal of Food and Nutritional Sciences, 2022)
The term "environmental concerns" refers to the negative consequences that people have on the planet and its natural systems. Although other natural factors can contribute to climate change, human conduct has caused greenhouse gases to rise. Climate change, environmental degradation, pollution, and resource depletion can all be the main environmental problems at the moment. The conservation movement movements against global warming, hereditarily engineered foods, and endangered animals. It also supports the protection of any biologically important natural areas. In this paper, the author discusses environmental concerns and explains how environmental elements affect both nature and people. Environmental concerns are the challenges and negative consequences brought about by human activity which is reckless and excessive use of natural resources environment. Researchers should be aware of the current environmental challenges we are experiencing as well as how to solve or mitigate them. Every person, animal, and other creatures on earth is affected by environmental issues including climate change, acid rain, urban development, garbage disposal, ozone layer depletion, and global warming.